Regular Languages Definable by Lindström Quantifiers - Ésik, Zoltán; Larsen, Kim G. (BRICS Report Series, 2003)
In our main result, we establish a formal connection between Lindström quantifiers with respect to regular languages and the double semidirect product of finite monoids with a distinguished set of generators. We use this correspondence to characterize the expressive power of Lindström quantifiers associated with a class of regular languages.